Relacja zasady skuteczności prawa unijnego i prawa do skutecznej ochrony sądowej – konieczność wyważenia dwóch wartości w prawie europejskim na przykładzie (w ramach) funkcjonowania systemu Europejskiego Nakazu Aresztowania (cz. I) - Ferenc, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The purpose of this article is, in particular, an attempt to answer the question how the European Court of Justice respects the standard of the right to effective judicial protection, (developed primarily by the European Court of Human Rights), within functioning the European Arrest Warrant Mechanism. The considerations will concern cases in which a conflict occurred, or a conflict could occur between the principle of effectiveness of European Union law and the right to effective judicial protection. In other words, it becomes legitimate to check whether the Court of Justice permits the restriction of the right to effective judicial protection for the full implementation of the principle of the effectiveness of European Union law. Relevant judgments of the Luxembourg court show that the practical application of the European Arrest Warrant instrument may raise serious doubts, especially in the sphere of the possibility of refusing its execution. The point of the considerations will be the ruling of the Court of Justice relating primarily to such elements of the right to effective judicial protection as the right to an independent and impartial court, the right of defense and the right to an effective remedy.
Keywords: European Arrest Warrant; the right to effective judicial protection; the principle of the effectiveness of EU law; European Convention on Human Rights; Charter of Fundamental Rights